Recognising poor black youth from rural communities in South Africa as epistemic contributors - Mathebula, Mikateko (Critical Studies in Teaching and Learning, 2023)
In South Africa, students who are poor, black and come from rural communities with poorly resourced schools are vulnerable to being victims of epistemic injustice. This is because they are usually seen as under-appreciated knowers who have low (English) language proficiency and deficits in academic literacy. In an attempt to provide a nuanced characterisation of youth from rural areas, this paper reflects on one student’s life-history interviews and his photo- story that form part of data collected since 2017 for Miratho – a project on achieved higher education learning outcomes for low-income university students. The paper uses a capabilities approach as an interpretive framework for the qualitative data and theorises that students’ linguistic capital and narrative capital are epistemic materials that can be mobilised into the ‘capability for epistemic contribution’ as conceptualised by Miranda Fricker. The paper thus makes a case for higher education researchers and educators to recognise poor black youth from rural communities as both givers and takers of knowledge or ‘epistemic contributors’. It argues that doing so constitutes an ethical response to the structural inequalities that limit equitable university access and participation for youth in this demographic.